Clinician's practices and perspectives regarding tobacco cessation in a teaching Hospital, Karnataka, India - M., Sumana; C. Y., Sreelatha; M., Sundar; Das, Narottam (International Journal Of Community Medicine And Public Health, 2017)
Background: Cessation of tobacco is important to prevent non-communicable diseases and mortality. Smokers frequently approach doctors for various health ailments. This opportunity can be utilized to give tobacco cessation advice. This study aims to assess the clinician’s practice perspectives barriers and need for the training related to tobacco cessation. Methods: A cross-sectional study was conducted to explore tobacco cessation practices of clinicians of a teaching hospital attached to Medical College in Hassan, Karnataka, India. Pre-tested, pre-structured self-administered questionnaire was distributed to all the clinicians in person. All the Professors, Associate Professors, Assistant Professors, Senior Residents and Junior Residents in the departments coming in contact with smokers were included in the study and patients were also interviewed to assess their smoking status, willingness to quit and counselling by physicians using pre-structured oral questionnaire. Results: Almost 84.4% of clinicians said they ask about smoking history but only 50.9% said they assess patients’ willingness to quit smoking. 37% assist patients to quit smoking and 29.8% arranged follow up visits. 25% of clinicians mentioned undergraduate and postgraduate training prepared them to help patients quit smoking. Remaining said it was inadequate. All agreed that it is their role to help, motivate, discuss, speak, refer and monitor patients who smoke to quit. Conclusions: Majority of the doctors believed that they play a very important role in tobacco cessation activities. There is a need for Undergraduate and postgraduate skill based training to assist patients quit the tobacco habit. The study showed a need for adherence and reinforcement of tobacco cessation guidelines.